A new three-term conjugate gradient-based projection method for solving large-scale nonlinear monotone equations - Koorapetse, Mompati; Kaelo, Professor (Mathematical Modelling and Analysis, 2019)
A new three-term conjugate gradient-based projection method is presented in this paper for solving large-scale nonlinear monotone equations. This method is derivative-free and it is suitable for solving large-scale nonlinear monotone equations due to its lower storage requirements. The method satisfies the sufficient descent condition , where  is a constant, and its global convergence is also established. Numerical results show that the method is efficient and promising.